PM urges families to spend quality time with children to keep them off drugs - Daily Express, (KK) (Sabah Publishing House Sdn. Bhd., 2014)
KUALA LUMPUR: All Malaysians are advised to spend quality time with their families and to communicate and pay extra attention to their children's feelings and requirements, so that they will not easily be influenced by negative elements. Prime Minister Datuk Seri Najib Tun Razak said cooperation from all quarters was vital to ensure that the Malaysian society would be free from threats of drugs, and that Malaysian children would grow up as a competitive and successful generation.